2018
DOI: 10.18202/jamal.2018.04.9004
|View full text |Cite
|
Sign up to set email alerts
|

Peran Corporate Governance dalam Meningkatkan Voluntary Disclosure

Abstract: Abstrak: Peran Corporate Governance dalam Meningkatkan Vo luntary Disclosure. Tujuan penelitian ini untuk menguji pengaruh sejumlah variabel corporate governance terhadap tingkat voluntary disclosure. Analisis data dilakukan dengan uji regresi linier ber ganda. Penelitian ini menunjukkan bahwa kepemilikan publik dan komite audit berpengaruh terhadap tingkat voluntary disclosure. Hal ini menunjukkan adanya peningkatan tuntutan voluntary disclosure. Selain itu, penelitian ini juga menemukan bahwa komite audit be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
4
0
5
Order By: Relevance
“…Although signaling theory indicates that voluntary report is not easy to be imitated, companies are willing to pay more in order to reduce negative image and get legitimacy by making sustainability report (Fatmawati, Astuti, & Suhardjanto, 2018;Wicaksono & Kholid, 2019). Neo-institutional theory calls this behavior as mimetic isomorphism.…”
mentioning
confidence: 99%
“…Although signaling theory indicates that voluntary report is not easy to be imitated, companies are willing to pay more in order to reduce negative image and get legitimacy by making sustainability report (Fatmawati, Astuti, & Suhardjanto, 2018;Wicaksono & Kholid, 2019). Neo-institutional theory calls this behavior as mimetic isomorphism.…”
mentioning
confidence: 99%
“…The previous study of the number of audit committees on disclosure showed mixed results. Fatmawati, Astuti, & Suhardjanto (2018) find the positive affected between sizes of the audit committees on the voluntary disclosure in Indonesia. Salehi & Shirazi (2016) showed significant positive effect between the size of the audit committee and the quality of financial disclosure.…”
Section: Hypotheses Developmentmentioning
confidence: 74%
“…The control variables in this study are the company size, leverage, external auditor, and industry type. Firm size was chosen as a control variable because some previous studies find that firm size influences the level of compliance disclosure (Bepari, Rahman, & Mollik, 2014;Sellami & Fendri, 2017;Fatmawati, Astuti, & Suhardjanto, 2018). Following Bepari, Rahman, & Mollik (2014) and Sellami & Fendri (2017), firm size is proxied by the natural logarithm of the total assets.…”
Section: Dwi Ernawati and Y Anni Aryanimentioning
confidence: 99%
“…This result is possible because the agency theory used to link the variable proportion of independent commissioners and the level of voluntary disclosure is weak. This statement is supported by Fatmawati et al, (2018) which implied that for both variables, it is better to use signalling theory for interested company to convey information that can increase company credibility although the information is not required to give a positive signal of the company. Furthermore, independent commissioners prefer to comply and make mandatory disclosures in accordance with regulations.…”
Section: Discussionmentioning
confidence: 90%